Interaction of neuropsychiatric symptoms with APOE e4 and conversion to dementia in MCI patients in a memory clinic: Neuropsychiatry and behavioral neurology/Mild cognitive impairment/Early symptomatic disease. (7th December 2020) - Valero, Sergi; Marquie, Marta; Rojas, Itziar; Moreno, Sonia; Espinosa, Ana; Orellana, Adelina; Montrreal, Laura; Hernandez, Isabel; Mauleon, Ana; Rosende‐Roca, Maitee; Alegret, Montserrat; Pérez‐Cordón, Alba; et al.
Abstract: Background: To the date, scarce studies have been focused in the impact of the convergence of neuropsychiatric symptoms (NPS) and APOE e4 on conversion to dementia in Mild Cognitive Impaired patients (MCI). None of them taking into account clinical settings of MCI patients. The objective was to determine the predictive value of additive and multiplicative interactions of NPS and APOE e4 status on the prediction of incident dementia among MCI patients monitored in a Memory Clinic. Method: 1512 patients (aged 60 and older) with prevalent MCI have been followed for a mean of 2 years. Neuropsychiatric symptoms were assessed at baseline using the Neuropsychiatric Inventory Questionnaire. Cox proportional hazards models were calculated, and several clinical variables were used as an adjusting factors, including the memory impairment condition, the attributed etiological pattern, and the antidepressant and anxiolytic medication used. Result: Additive interactions for depression, apathy, anxiety, agitation, appetite, or irritability and a positive ε4 carrier status were obtained, increasing significantly the hazard ratios of incident dementia (HR range 1.3 – 2.03). Conclusion: Synergistic interactions between NPS and APOE e4 are identified among MCI patients when predicting incident dementia. The combination of the behavioral status and the genetic trait could be considered a useful strategy to identify the most vulnerable MCI patients to dementia conversion in a Memory Clinic.